Near‐Infrared Quadrupolar Chromophores Combining Three‐Coordinate Boron‐Based Superdonor and Superacceptor Units. Issue 19 (3rd April 2019) - Stennett, Tom E.; Bissinger, Philipp; Griesbeck, Stefanie; Ullrich, Stefan; Krummenacher, Ivo; Auth, Michael; Sperlich, Andreas; Stolte, Matthias; Radacki, Krzysztof; Yao, Chang‐Jiang; Würthner, Frank; Steffen, Andreas; et al.
Abstract: Herein, two new quadrupolar acceptor‐π‐donor‐π‐acceptor (A‐π‐D‐π‐A) chromophores have been prepared featuring a strongly electron‐donating diborene core and strongly electron‐accepting dimesitylboryl (BMes2 ) and bis(2, 4, 6‐tris(trifluoromethyl)phenyl)boryl (B F Mes2 ) end groups. Analysis of the compounds by NMR spectroscopy, X‐ray crystallography, cyclic voltammetry, and UV/Vis‐NIR absorption and emission spectroscopy indicated that the compounds have extended conjugated π‐systems spanning their B4 C8 cores. The combination of exceptionally potent π‐donor (diborene) and π‐acceptor (diarylboryl) groups, both based on trigonal boron, leads to very small HOMO–LUMO gaps, resulting in strong absorption in the near‐IR region with maxima in THF at 840 and 1092 nm and very high extinction coefficients of ca. 120 000 m −1  cm −1 . Both molecules also display weak near‐IR fluorescence with small Stokes shifts. Abstract : Double B‐side : A combination of extremely potent boron‐based donor and acceptor moieties in a conjugated system leads to quadrupolar chromophores with extremely small HOMO–LUMO gaps, which display highly unusual near‐IR absorption and emission. Unusually for diborenes, the compounds can be reduced electrochemically to their radical anions.